Current-induced fingering instability in magnetic domain walls - Gorchon, J. (2015)
The shape instability of magnetic domain walls under current is investigated in a ferromagnetic (Ga,Mn)(As,P) film with perpendicular anisotropy. Domain wall motion is driven by the spin transfer torque mechanism. A current density gradient is found either to stabilize domains with walls perpendicular to current lines or to produce fingerlike patterns, depending on the domain wall motion direction. The instability mechanism is shown to result from the nonadiabatic contribution of the spin transfer torque mechanism.